THE KNOWLEDGE AND EXPERIENCE IN FINANCE TOWARD INVESTMENT PLANNING MOTIVE: THE MODERATION ROLE OF SELF-CONTROL - Rahayu, Ruci Arizanda; Hariyanto, Wiwit; Abidin, Fityan Izza Noor (International Journal Multidisciplinary (IJMI), 2024)
This research aims to examine the moderation of self control which affect investment planning motive on civil servants in Sidoarjo. The well executed financial management is not only managing financial income and daily needs, but it needs to be prepared for the future financial management if someday a person or individual needs more financial income. For example in the way to invest. Along with investment, an individual will get profits or benefits in the future. Analysis tool that is used in this research is questionnaire sheet that have already conveyed to 77 respondents and purposive sampling as the sampling approach. To examine the research hypothesis, the researcher use Partial Least Square (PLS) with Smart PLS software, version 3.2.7. The output of this research is an article within index SINTA (Science and Technology Index) 3 (third rank) journal, national seminar article, and intellectual property rights. Technology readiness level which is tragetted in the research is 1 – 4. The urgency in this study is because of the tendency of each individual nowdays, moreover they who have a family, generally have a financial purpose in the future. Nevertheless, there are pletiful people who can not fulfil their dream because of financial issues to achieve that financial goals.